Successful Manager's Handbook - Ali Moi (Dorling Kindersley, 2002)
This text is a practical guide to effective management techniques, aimed at all managers seeking to improve in key areas of performance. It combines the work of experts in an easy-to-follow, practical format, including over 1200 power tips for boosting the efficiency of your team. Topics covered include: getting organized; writing effectively; thinking creatively; influencing people; developing NLP skills; dealing with difficult people; appraising staff; managing public relations and putting customers first.